2018
DOI: 10.3727/096504017x15144741233346
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-103 Promotes Proliferation and Inhibits Apoptosis in Spinal Osteosarcoma Cells by Targeting p57

Abstract: Osteosarcoma is one of the most aggressive malignancies with poor prognosis rates. Many studies have demonstrated that miRNAs were involved in osteosarcoma, but the role of miR-103a in osteosarcoma remains elusive. In this study, we detected the expression levels of miR-103 in osteosarcoma and non-osteosarcoma tissues and cell lines. The binding effect of miR-103 on p57 was detected by luciferase reporter assay. After altering expressions of miR-103 or p57, viability, migration, invasion, and apoptosis of MG63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, it should be mentioned that LATS2 is not the sole target of miR103, as several other targets have been identified in other cancer cells, including A-kinase anchoring protein 12 (AKAP12), vascular endothelial growth factor (VEGF), Wnt3a and p57 ( 36 - 38 ). Thus, it is possible that miR-103 can promote the proliferation, migration, invasion and EMT of HCC cells through other targets.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that LATS2 is not the sole target of miR103, as several other targets have been identified in other cancer cells, including A-kinase anchoring protein 12 (AKAP12), vascular endothelial growth factor (VEGF), Wnt3a and p57 ( 36 - 38 ). Thus, it is possible that miR-103 can promote the proliferation, migration, invasion and EMT of HCC cells through other targets.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs bind with 3'UTR of target gene to inhibit the translation or degradation of target mRNA [16]. Aberrant expressions of miR-103a-3p are in a variety of tumors, such as high expression in osteosarcoma [17], but low expression in glioma stem cells and glioma tissue [18]. Research found that miR-103a-3p was an important molecule in the process of glioblastoma [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-103a-3p was also negatively correlated with LATS1 in thyroid cancer tissues. Previous studies have shown that miR-103a-3p can activate the JNK/STAT and the mTOR signaling pathways to inhibit apoptosis by targeting p57 [28], and promote cell proliferation in gastric cancer by targeting activating transcription factor 7 [12]. These studies demonstrate that miRNAs play a key role in the complex gene regulatory networks by regulating their targets.…”
Section: Discussionmentioning
confidence: 67%